Comparative learning holding on satisfaction, interest in learning, and academic performance of student - Fathonah, Siti; Wahyuningsih, Wahyuningsih; Rosidah, Rosidah; Triatma, Bambang; Astuti, Romiyatun Mijiling; Fadilah, Ahmad; Fatima, Cikha Yulia; Ciskawati, Dyah Ayu (Journal of Education and Learning (EduLearn), 2025)
The COVID-19 virus pandemic limits the movement of activities and learning is carried out online, followed by blended. After returning to normal offline. The research objectives are i) to analyze satisfaction, interest in learning and academic performance with online, blended and offline learning and ii) to differentiate between study programs in the Family Welfare Education. The research subjects were 5th semester students, cross-sectional study. Satisfaction, interest in learning and academic performance of students were measured using a questionnaire with a Likert scale of 1-5. Data analysis was descriptive percentages, difference tests with Kruskal-Wallis followed by Mann-Whitney, and correlation with the Gamma test. The level of student satisfaction with online, blended and offline learning is in the satisfied category. Interest in learning and academic performance in the good category. There are significant differences in the level of satisfaction, interest in learning and academic performance with online, blended and offline learning, as well as between study programs. There is a high relationship between the level of satisfaction and interest in learning with academic performance. The comparison of learning holding differs significantly in levels of satisfaction, interest, academic performance and between study programs, but in the same category (good). The best learning holding is offline.